2011
DOI: 10.1007/s10841-011-9443-2
|View full text |Cite
|
Sign up to set email alerts
|

Patch shape alters spider community structure: links between microhabitat choice and sensitivity to increased edge habitat

Abstract: Increased edge effects in fragmented habitats can affect the abundance of edge-dwelling organisms, but these impacts may depend on the biological attributes of species. Microhabitat choice, a species characteristic that reflects combinations of biological traits, may affect the ability of peripheral species to take advantage of increased edge habitat in the presence of edge effects. In this field study, we built artificial shrub modules designed to encourage web spiders to build webs on the periphery. While mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…For example, some spider species might consider solar panels as discrete habitat patches, and web spiders at habitat edges are expected to increase because of the facilitation to build webs in anthropic environments and to improve their fitness (Wise 2006). As a result from the increase in edge habitation, there were changes in species interactions which may be beneficial or detrimental to edge organisms depending on their intrinsic ecological traits (Cobbold & Supp 2012). The latter supports the idea that the structure of fixed-mounts determined the spatial assemblage pattern rather than abiotic conditions.…”
Section: Biotic Environment Of Solar Power Plantssupporting
confidence: 52%
“…For example, some spider species might consider solar panels as discrete habitat patches, and web spiders at habitat edges are expected to increase because of the facilitation to build webs in anthropic environments and to improve their fitness (Wise 2006). As a result from the increase in edge habitation, there were changes in species interactions which may be beneficial or detrimental to edge organisms depending on their intrinsic ecological traits (Cobbold & Supp 2012). The latter supports the idea that the structure of fixed-mounts determined the spatial assemblage pattern rather than abiotic conditions.…”
Section: Biotic Environment Of Solar Power Plantssupporting
confidence: 52%
“…Spider and ground beetle communities respond structurally to environmental change, indicating that they can provide valuable information for ecological impact assessment [101]. Both Tetragnathidae and Lycosidae are regarded as adequate biological indicators of habitat modification due to their potential to provide early warnings of environmental change [115][116][117]. These predatory invertebrates (e.g., tetragnathid and lycosid spiders, as well as carabid and staphylinid beetles) may be important sentinels of change because of their importance in controlling crop pest populations [92,118].…”
Section: Management Implicationsmentioning
confidence: 99%
“…Collinge and Palmer (2002) showed that movement of grounddwelling beetles across patch boundaries may be affected by patch shape. Habitat patch shape seems to have a significant effect on the community structure of predators by modifying their microhabitat choice (Cobbold & Supp, 2012). In a word, patch shape may play an important role among defoliators and natural enemies (Olson & Andow, 2008).…”
Section: Landscape Complexitymentioning
confidence: 99%